The Secular Scripture and Other Writings on Critical Theory, 1976-1991 - Frye, Northrop (Book collections on Project MUSE., 2005)
His new edition in the Collected Works of Northrop Frye series brings The Secular Scripture together with thirty shorter pieces pertaining to literary theory and criticism from the last fifteen years of Frye's life.